Moral Reasoning Among Croatian Students of Different Academic Orientations - Tokić, Andrea; Matilda Nikolić (European Journal of Multidisciplinary Studies, 2017)
Previous studies demonstrated that different academic contexts could have different effects on moral development, i.e. in most cases formal education enhances moral reasoning, but sometime erodes it (for example for medical students). The aim of this study was to examine differences in moral reasoning among students of different academic disciplines (health care, law, social sciences and humanities). In research participated 386 students (Mage=23,12): 154 law students, 55 nursing students, 123 other social sciences students, a 53 humanities students. Participants took Test of Moral Reasoning (TMR) (Prorokovi?, 2016) which measures index of moral reasoning (in range from 0 to 1), and idealistic orientations (humanistic and conservative). The results showed that there was no difference in the moral reasoning index among students of different academic orientations. Furthermore, students of different academic disciplines differed in the humanistic orientation in a way that students of social studies were more humanistically oriented than law students. Some of the possible explanations for the lack of differences with regard to academic orientations is that overall stimulating environment that college provides is perhaps more important for moral reasoning development than specific academic contexts. Findings of this study are consistent with the findings of some of the previous studies.